Grassroots Conceptions of Democracy in the Global South - Claudio, Lisandro E. (Archīum Ateneo, 2017)
Excerpt: One of this journal’s primary commitments has been to represent the Global South, while attending to the need to continually critique political praxis. Three of the articles in this double issue are consistent with this thrust. Trent Brown’s account of participatory rural development in Tamil Nadu, Mathieu John’s analysis of digital activism in war-torn Syria, and Dennis Blanco’s challenges for those combatting human trafficking, all emphasize the need to perennially rethink the givens of various forms of activism. All three articles, moreover, implicitly or explicitly, theorize concepts of popular participation, and democracy.